The economic determinants of bioenergy trade intensity in the EU-28: a co-integration approach - Alsaleh, Mohammed; Abdul Samad @ Iammi, Abdul Rahim (MDPI, 2018)
This paper examines the dynamic effect of the economic determinants on bilateral trade intensity of the European Union (EU) region’s bioenergy industry outputs. The authors adopt the panel co-integration model approach to estimate annual trade intensity data of the EU-28 countries’ bioenergy industry outputs from 1990 to 2013. This study investigated the long-term influence of the rate of real exchange, gross domestic product (GDP), and export price on the trade intensity of bioenergy industry applying fully modified oriented least square (FMOLS), dummy oriented least square (DOLS), and pooled mean group (PMG) models. In the current study, the findings boost the empirical validity of the panel co-integration model through FMOLS, indicating that depreciation has improved the trade intensity. This study has further investigated, through the causality test, a distinct set of countries. FMOLS estimation does find proof of the long run improvement of trade intensity. Thus, the result shows that the gross domestic product (GDP) and the real exchange rate have a positive and noteworthy influence on the EU-28 region trade intensity of the bioenergy industry. Moreover, the export price affects negatively and significantly the trade intensity of the bioenergy industry in the EU-28 countries.